Fibroblast growth factor receptor 3 activates a network of profibrotic signaling pathways to promote fibrosis in systemic sclerosis - Chakraborty, Debomita; Zhu, Honglin; Juengel, Astrid; Summa, Lena; Li, Yi-Nan; Matei, Alexandru-Emil; Zhou, Xiang; Huang, Jingang; Thuong Trinh-Minh; Chen, Chih-Wei; Lafyatis, Robert; Dees, Clara; et al. (Science Translational Medicine, 2020)
Aberrant activation of fibroblasts with progressive deposition of extracellular matrix is a key feature of systemic sclerosis (SSc), a prototypical idiopathic fibrotic disease. Here, we demonstrate that the profibrotic cytokine transforming growth factor. selectively up-regulates fibroblast growth factor receptor 3 (FGFR3) and its ligand FGF9 to promote fibroblast activation and tissue fibrosis, leading to a prominent FGFR3 signature in the SSc skin. Transcriptome profiling, in silico analysis and functional experiments revealed that FGFR3 induces multiple profibrotic pathways including endothelin, interleukin-4, and connective tissue growth factor signaling mediated by transcription factor CREB (cAMP response element-binding protein). Inhibition of FGFR3 signaling by fibroblast-specific knockout of FGFR3 or FGF9 or pharmacological inhibition of FGFR3 blocked fibroblast activation and attenuated experimental skin fibrosis in mice. These findings characterize FGFR3 as an upstream regulator of a network of profibrotic mediators in SSc and as a potential target for the treatment of fibrosis.
CRIS-Team WoS Importer:2020-10-16